Recurrent neonatal gastric perforation: An unusual case report: Perforación gástrica neonatal recurrente: Reporte de un caso inusual - Velarde-Paredes, Percy Edilberto (2023)
Neonatal gastric perforation is a rare but potentially fatal pathology; its recurrence is even more infrequent, and there are few reports in the international literature. We present the case of a premature newborn (32 weeks) and low birth weight (1725g) who, on the first day of life, presented a surgically corrected gastric perforation and on the fourth postoperative day was re-operated with a presumed diagnosis of gastric raffia dehiscence, finding a new gastric perforation, which was surgically repaired. On both occasions, the surgical intervention was early. The subsequent evolution and outcome were favorable.